Interim Report of the Study Team on the Machinery for Planning Submitted to the Administration Reform Commission - Administrative Reforms Commission (Administrative Reforms Commission, Government of India, 1967)
Our Study Team has been given the task of studying the machinery for planning at all levels, i.e., "planning organisation and procedures at the Centre and in the States and relationship of the Planning Commission at the Centre and the planning agencies in the States with other agencies". the Study Team is expected, in regard to this subject, "to ascertain facts, locate the principal problem areas, examine solutions for the problems and make recommendations for the consideration of the Administrative Reforms Commission."